O alinhamento de valores pessoais e organizacionais: um estudo de caso em uma empresa de energia - Hallak, Beatriz Resende (2008)
The present dissertation aims at investigating whether the firm under analysis aligns its organizational and personal values, and the level at which these values are spread within the firm. The main theoretical underpinning of the dissertation consists of Richard Barrett s (2006) model of the seven levels of consciousness itself based on Abraham Maslow s (1954) model of the hierarchy of needs which is extended to higher levels. Research was carried out in two fronts: documentary investigation and field work, the latter comprising the application of a structured questionnaire derived from the theoretical literature. The research revealed the ten main current personal and organizational values at the firm, as well as the ideal organizational values. These were classified as either positive or potentially limiting, and were distributed among the seven levels of conscience, for both the sample as a whole and according to a few chosen criteria: age group, gender, position and time in the company. Results show that there are significant differences among the several values that were pointed out in the three dimensions and the recommendations involve a set of actions that may contribute to enhance management of the firm. Further research on this subject and the use of the theoretical model to analyze other organizational issues are also suggested